PENGARUH UMUR PERUSAHAAN, KUALITAS AUDIT DAN KOMITE AUDIT TERHADAP AUDIT REPORT LAG - Fatmawati, Fatmawati; Khuluqi, Khusnul (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to explain and provide empirical evidence regarding the influence of company age, audit quality and audit committee on Audit Report Lag. This study was conducted by analyzing the financial statements of companies in the Energy sector listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The sample used in this study was 86 Energy companies for the period 2019 to 2023 using a purposive sampling technique. The data used in this study are secondary data in the form of annual reports from each company that has been used as a research sample. Based on the results of this study, it shows that (1) Company Age, Audit Quality, and Audit Committee, simultaneously have a significant effect on Audit Report Lag, (2) Company Age has a significant effect on Audit Report Lag, (3) Audit Quality does not have a significant effect on Audit Report Lag, and (4) Audit Committee does not have an effect on Audit Report Lag.